The rocky desertification management in Guizhou province under the localized governance system - Yuan, Liang; Liu, Wendao; Su, Shan; Chen, Zhuo (Frontiers in Environmental Science, 2022)
Guizhou Province has shown remarkable rocky desertification management results in this century. However, under the localized governance system, the division of Guizhou's rocky desertification management zoning map has also shown its drawbacks. The conflicts arising from the localized governance system in China and rocky desertification management in Guizhou are mainly demonstrated by the following manifestations: 1) areas originally required for integrated governance are divided by different municipal administrative affiliations, resulting in the inability to coordinate governance; 2) the same administrative affiliation of the counties is divided into different areas of governance. The key factor is the differentiation of governance due to administrative division, including constraints such as differences in the focus of governance, governance tools and governance philosophy. Based on this, it is recommended that local governance focus on cross-administrative cooperation as well as the reasonable adjusting and promoting of governance boundaries.